Shifting categories of work unsettling the ways we think about jobs, labor, and activities - Zimmermann, Bénédicte; Herzog, Lisa 1983- (New York, NY Routledge, 2023)
Shifting Categories of Work illuminates the ways in which our societies categorize work. Written by sociologists, philosophers, historians, and anthropologists as well as management and legal scholars, the contributions in this volume contrast different cultural practices and frameworks of categorizing work"--
Includes bibliographical references and index.
Keywords: Labor; Work